Structural performance assessment before strengthening of historic Structures: A case study of the historical S,erafettin mosque in Turkey - Çakır, Ferit; Odabas, Anil; Zulfikar, Can; Zeyrek, Selim; Kir, Gul (Pergamon-Elsevier Science Ltd, 2023)
Historical masonry structures are invaluable remnants of the past, representing significant cultural heritage within societies. However, the ravages of time and natural disasters have led to the collapse or severe deterioration of numerous structures worldwide. Therefore, safeguarding these structures and passing them down to future generations necessitates effective strengthening measures. In this purpose, evaluating the structural performance of existing buildings constitutes a crucial aspect of such preservation efforts. While numerous countries have conducted studies in this domain, no universally accepted method exists to date. This study focuses on assessing the structural performance of historical masonry structures prior to retrofitting interventions. Specifically, the S,erafettin Mosque, an architectural gem dating back to the late 12th century in Konya, was selected as a case study for strengthening. The performance evaluation process entailed seven key steps: (Step-1) Structural System Investigation, (Step-2) Damage Assessment Studies, (Step-3) Seismicity Analysis of the Region, (Step-4) Geotechnical Field Tests, (Step-5) Geotechnical Laboratory Tests, (Step-6) Ambient Vibration Tests (AVTs), and (Step-7) Finite Element Analysis. This study highlights substantial contributions and novel findings resulting from a comprehensive analysis performed on a notable historical mosque. The precise examination of a significant historical structure emphasizes the exceptional importance and quality of this research. Additionally, a wide range of investigations were conducted on both the site and the building, with a strong emphasis on presenting these critical findings in a systematic manner. By incorporating these essential details, this study greatly contributes to the comprehension and preservation of historical structures, offering valuable insights for future research and conservation endeavors.
Keywords: Masonry Structures; Structural Performance Evaluation; Geotechnical Parameters; Soil -Foundation -Structure Interaction; Ambient Vibration Test; Finite Element Analysis